Radiological examination of the articular eminence morphology using cone beam CT - Sümbüllü, MA (The British Institute of Radiology., 2012)
OBJECTIVE: The purpose of the present study was to investigate the articular eminence inclination and height according to age and gender in patients with temporomandibular joint (TMJ) dysfunction and healthy controls using cone beam CT (CBCT). METHODS: The measurements were performed on CBCT records of 52 TMJ dysfunction patients (11 males and 41 females) and 41 control patients (17 males and 24 females). The eminence inclination and height were measured on the CBCT images. RESULTS: The eminence inclination and height values were higher in males than in females in both TMJ dysfunction patient and control groups; however, these differences were not statistically significant (p>0.05). While no statistically significant differences were found in the eminence inclination and height values between the age groups (p>0.05) in the TMJ dysfunction patient group, there were statistically significant differences in the control group. The eminence inclination was highest between the ages of 21 and 30 years and showed a decrease after the age of 30 years. Additionally, the eminence inclinations of the control patients were statistically higher than those of the TMJ dysfunction patients. CONCLUSION: There were no statistically significant differences in eminence inclination and height according to gender. The eminence inclination reaches its highest value between the ages of 21 and 30 years and shows a decrease after the age of 31 years in healthy patients. The eminence inclination was steeper in healthy control patients than in patients with TMJ dysfunction.